2017
DOI: 10.1186/s12865-017-0202-3
|View full text |Cite
|
Sign up to set email alerts
|

Poly I:C induces collective migration of HaCaT keratinocytes via IL-8

Abstract: BackgroundDelayed wound healing reduces the quality of life (QOL) of patients. Thus, understanding the mechanism of wound healing is indispensable for better management. However, the role of innate immunity in wound healing is thus far unknown. Recently the involvement of TLR3 in wound healing has been evaluated. The systemic administration of polyriboinosinic-polyribocytidylic acid (poly I:C ; a substitute for viral dsRNA and a ligand of toll-like receptor 3), enhances wound healing in vivo. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Further researches have elucidated suppression of EMT and subsequent inhibition of cell proliferation and invasion 59 . Furthermore, EMT could be reversible even though mesenchymal to epithelial transition was often an incomplete process 60 62 . In our study, we found that downregulation of PLK4 depressed EMT program in NB cells, including upregulation of the epithelial marker E-cadherin, as well as downregulation of mesenchymal markers (N-cadherin, Slug, and vimentin).…”
Section: Discussionmentioning
confidence: 99%
“…Further researches have elucidated suppression of EMT and subsequent inhibition of cell proliferation and invasion 59 . Furthermore, EMT could be reversible even though mesenchymal to epithelial transition was often an incomplete process 60 62 . In our study, we found that downregulation of PLK4 depressed EMT program in NB cells, including upregulation of the epithelial marker E-cadherin, as well as downregulation of mesenchymal markers (N-cadherin, Slug, and vimentin).…”
Section: Discussionmentioning
confidence: 99%
“…32 Briefly, MS74 cells were grown to confluence in 24-well microplate (Falcon, Corning, NY, USA) with 1 mL of the medium described above. 32 Briefly, MS74 cells were grown to confluence in 24-well microplate (Falcon, Corning, NY, USA) with 1 mL of the medium described above.…”
Section: Scratch Assaymentioning
confidence: 99%
“…The scratch assay was performed as previously described. 32 Briefly, MS74 cells were grown to confluence in 24-well microplate (Falcon, Corning, NY, USA) with 1 mL of the medium described above. A linear scratch was made using a 2-mm-wide Cell Scratcher (Iwaki Glass, Chiba, Japan), and the wells were washed once with phosphate buffered saline (PBS).…”
Section: Scratch Assaymentioning
confidence: 99%
“…Even if further in vivo studies should be conducted to confirm their potential therapeutic use, it will be of interest to firstly verify the reproducibility of the observed effects on HaCat cell line, also on primary keratinocytes, as well as other cell types involved in skin wound healing process (i.e., fibroblasts, endothelial cells), focusing on the biomolecular mechanism behind the observed effects. In this regard, considering the role attributed to the pro-inflammatory cytokines IL-6 and IL-8 in the tissue repair process [44][45][46] as well their association with NOS2 expression in different cellular models [47][48][49][50][51], our preliminary results ( Figure S1, Supplementary Materials) show that S. thermophilus, L. plantarum, and L. acidophilus samples, able to positively modulate NOS2/NO system and stimulate scratched monolayer repair, significantly increased the secretion of these two cytokines by HaCat; conversely B. infantis, B. breve, and B. longum, which caused a reduction of NOS2 expression and activity, also led to decreased levels of IL-6 and IL-8. L. bulgaricus, also in this context, did show no effect.…”
Section: Discussionmentioning
confidence: 99%